2021
DOI: 10.7759/cureus.19394
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical Increase in Body Mass Induced by Beta-Guanidinopropionic Acid in Juvenile Spontaneously Hypertensive Rats

Abstract: Background The adenosine triphosphate (ATP) regenerating enzyme creatine kinase (CK) is intimately involved in blood pressure generation. Consequently, the creatine transporter and CK inhibitor beta-guanidinopropionic acid (GPA) successfully reduced blood pressure in 16-week-old spontaneously hypertensive rats (SHR), but GPA may cause growth retardation in juvenile mammals. This report considers a serendipity observation of paradoxical growth increase after using GPA to prevent hypertension in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…β -Guanidinopropionic acid (GPA) is an endogenous AMPK agonist. In recent years, it has been found that GPA can competitively inhibit creatine kinase from reducing blood pressure in rats with essential hypertension [ 34 ]. GPA was found to be safe and well-tolerated in human experiments [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…β -Guanidinopropionic acid (GPA) is an endogenous AMPK agonist. In recent years, it has been found that GPA can competitively inhibit creatine kinase from reducing blood pressure in rats with essential hypertension [ 34 ]. GPA was found to be safe and well-tolerated in human experiments [ 35 ].…”
Section: Discussionmentioning
confidence: 99%